Teaching Arabic At Maqnaul Ulum Islamic Boarding School Sukowono Jember - Angga Sofyan Arifin (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2021)
Learning is an activity inseparable from human life and is carried out by everyone to obtain new knowledge that can change individual behavior. The problems raised in this study are about implementing Arabic language learning in Maqnaul Ulum Islamic boarding school and evaluating Arabic language learning in Maqnaul Ulum Islamic boarding school. The theory used in this study is a qualitative descriptive theory, namely the Miles and Huberman theory; researchers use this theory because researchers carry out the data analysis process at the time of data collection after data collection research. Implementing Arabic language learning at Maqnaul Ulum Islamic boarding school is done twice daily for 2 hours. The first is learning after the Fajr prayer, where the focus of learning is maharoh to train to speak, and the second is learning after the Isha prayer, where learning is to teach writing and reading. The evaluation of Arabic learning in Maqnaul Ulum Islamic boarding school is by examination and punishment. التعلم هو نشاط لا ينفصل عن حياة الإنسان ويقوم به الجميع لاكتساب المعرفة الجديدة يمكنها تغيير السلوك الفرد . كانت مشكلة البحث في هذا البحث عن تنفيذ تعليم اللغة العربية في المعهد مقنع العلوم الإسلامية و تقويم تعليم اللغة العربية في المعهد مقنع العلوم الإسلامية.والمناهج المستخدمة في هذا البحث هي المناهج الكيفي الوصفية. المنهج المستخدم فى هذا البحث هو طريقة ميلز وهوبارمان (Miles & Huberman) ومر هذا البحث بثلاث مراحل هي النشاط في تحليل تخفيض البيانات واستعراضها كخلاصتها. تستخدمها الباحث لأنه عملية تحليل البيانات التى تعملها الباحث في وقت جمع البيانات وبعد انتهاء جمع البيانات. تنفيذ تعليم اللغة العربية في المعهد مقنع العلوم الإسلامي مرتين في يوم واحد، بالوقت التعليم ساعتين تقريبًا. الأول، التعليم بعد الصبح، تركيز التعليم على تدريب الكلام. الثاني، التعليم بعد العشاء، تركيز التعليم على تدريب الكتابة والقراءة. اما تقويم تعليم اللغة العربية في المعهد مقنع العلوم الإسلامي وهي على شكل الإختبارات والعقوبات.